Evaluation of Oral Hygiene Practices, Oral Health Status and Behaviours among Dental Students at Qassim University (Bangladesh Journal of Medical Science, 2023)
Objectives: current study was carried out to evaluate the pattern and differences concerning oral health attitudes and behavior pattern between students studying in pre-clinics with higher class dental students in clinics at Qassim University.Method: A cross-sectional study through survey in Qassim University dental clinics in 2020-2021, among dental students, All the 100 participants undergone a self-administered questionnaire survey followed by a dental checkup to access the dental health and oral hygiene status.Result: Caries prevalence revealed a mean DMFT 5.99 teeth. The significant differences were found in mean of total DMFT score and its ‘Decayed’ component. Gingival index score was 0.72 ± 0.37 which indicate good gingival condition. There’s a highly statistically significant difference among the male when compared with female students (p>0.001). Plaque index score was 0.92 ± 0.33, 72% of the students had good oral hygiene. 86% reported they brush at least once a day. We observed significant difference from groups male to female groups (p=0.001). Flossing been adopted by 59% of students. Female students reported significantly higher frequencies (p=0.005) Conclusions: This study recommends the needs to have extensive program for the dental students from the beginning to enhance the selfcare behaviors and also the oral health status.Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.33-41